'I didn't see that coming': simulated visual fields and driving hazard perception test performance. (3rd August 2016) - Glen, Fiona C; Smith, Nicholas D; Jones, Lee; Crabb, David P
Abstract: Background: Evidence is limited regarding specific types of visual field loss associated with unsafe driving. We use novel gaze‐contingent software to examine the effect of simulated visual field loss on computer‐based driving hazard detection with the specific aim of testing the impact of scotomata located to the right and left of fixation. Methods: The 'hazard perception test' is a component of the UK driving licence examination, which measures speed of detecting 15 different hazards in a series of real‐life driving films. We have developed a novel eye‐tracking and computer set up capable of generating a realistic gaze‐contingent scotoma simulation (GazeSS) overlaid on film content. Thirty drivers with healthy vision completed three versions of the hazard perception test in a repeated measures experiment. In two versions, GazeSS simulated a scotoma in the binocular field of view to the left or right of fixation. A third version was unmodified to establish baseline performance. Results: Participants' mean baseline hazard perception test score was 51 ± 7 (out of 75). This reduced to 46 ± 9 and 46 ± 11 when completing the task with a binocular visual field defect located to the left and right of fixation, respectively. While the main effect of simulated visual field loss on performance was statistically significant (p = 0.007), there were no average differences in the experimental conditions where a scotoma was located in the binocular visual field to the right or left of fixation. Conclusion: Simulated visual field loss impairs driving hazard detection on a computer‐based test. There was no statistically significant difference in average performance when the simulated scotoma was located to the right or left of fixation of the binocular visual field, but certain types of hazard caused more difficulties than others.